2023
DOI: 10.1111/jar.13090
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of the dynamic risk outcome scales (DROS) for recidivism in (forensic) clients with mild intellectual disabilities or borderline intellectual functioning

Abstract: Background The dynamic risk outcome scales (DROS) was developed to assess treatment progress of clients with mild intellectual disability or borderline intellectual functioning using dynamic risk factors. We studied the predictive value of the DROS on various classifications and severity levels of recidivism. Method Data of 250 forensic clients with intellectual disabilities were linked to recidivism data from the Judicial Information Service in the Netherlands. Receiver operating characteristics (ROC) analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Based on 47 studies with age information, the median age was 35 years (IQR [33][34][35][36][37][38]. Studies were conducted in 12 countries-Austria, 34 Australia, [35][36][37] Belgium, [38][39][40][41][42] Canada, [43][44][45][46][47][48][49][50][51] Denmark, [52][53][54] Finland, 50,55 Germany, 50,56 Japan, 57 Netherlands, 3,[58][59][60][61][62][63][64][65][66][67] Sweden, 50,[68][69][70][71][72][73][74] the UK,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on 47 studies with age information, the median age was 35 years (IQR [33][34][35][36][37][38]. Studies were conducted in 12 countries-Austria, 34 Australia, [35][36][37] Belgium, [38][39][40][41][42] Canada, [43][44][45][46][47][48][49][50][51] Denmark, [52][53][54] Finland, 50,55 Germany, 50,56 Japan, 57 Netherlands, 3,[58][59][60][61][62][63][64][65][66][67] Sweden, 50,[68][69][70][71][72][73][74] the UK,…”
Section: Resultsmentioning
confidence: 99%
“…Based on 47 studies with age information, the median age was 35 years (IQR 33–38). Studies were conducted in 12 countries—Austria, 34 Australia, 35 , 36 , 37 Belgium, 38 , 39 , 40 , 41 , 42 Canada, 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 Denmark, 52 , 53 , 54 Finland, 50 , 55 Germany, 50 , 56 Japan, 57 Netherlands, 3 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 Sweden, 50 , 68 , 69 , 70 , 71 , 72 , 73 , 74 the UK, 75 , 76 , 77 , 78 , 79 , 80 and the USA 81 , 82 —all high-income economies ( appendix p 4 ). 83
Figure 1 PRISMA flow diagram
…”
Section: Resultsmentioning
confidence: 99%
“…Research has shown that the DROS, with 14 subscales (i.e., dynamic risk factors) and a total score, is reliable and valid (see Delforterie et al, 2020; Drieschner, 2014) and has a good predictive value for aggressive behaviour within treatment facilities (Drieschner et al, 2013). In addition, a DROS recidivism subscale including the subscales Hostility , Impulsivity and Tendency to substance abuse of the DROS predicted recidivism with medium to large effects (Delforterie et al, 2023).…”
Section: Introductionmentioning
confidence: 99%